Thermodynamic Functions Molecular Polarizability of 2,6-dichloro-4-fluoro Phenol - Malik, Dr. Surbhi; Singh, D.P.; Kumar, Sarvindra (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The Laser-Raman and FT-IR spectra of 2,6-dichloro-4-fluoro phenol (2,6,4-DCFP) have been recorded. The thermodynamic functions, namely, the enthalpy, the heat capacity, the free energy and entropy of 2,6,4-DCFP have been calculated at a pressure of 1 atmosphere in the temperature range 200-1500 K under rigid rotor harmonic oscillator. The one-dimensional semi-empirical delta-function model of chemical binding has been used to evaluate the average molecular polarizability of 2,6,4-DCFP.